Performance comparison of Ga and Ga/La alloy layered active magnetic regeneration beds in a rotary magnetic refrigeration prototype - Nattapol Dedruktip (2022)
A magnetocaloric material (MCE) is a material whose temperature changes under varying magnetic field. It has been used as a solid-state refrigerant in a magnetic refrigeration prototype. This work reported the design and development of a rotary active magnetic regeneration (AMR) prototype with a magnetic field amplitude of 0.625 T. The purpose of this study is to compare the performances between two different magnetocaloric AMR beds: Gadolinium (Gd) AMR bed and Gd/Lanthanum (La)-alloy layered AMR bed. The Gd/La alloy layered AMR bed is composed of 5 segments of MCE materials with different Curie temperature (Tc). All Gd and La-alloy materials used in this study were irregular-shape particles with particle sizes smaller than 200 µm. The MCE materials were packed in an AMR bed. The cooling performance of the 40 mm Gd/La layered AMR bed, 80 mm Gd/La layered AMR bed, 80 mm Gd AMR bed were tested and compared by adjusting the heat-exchange fluid flow rate and the frequency of magnetization. At zero thermal load, the 40 mm Gd/La layered bed resulted in the temperature span of 2 °C, which is relatively similar to that of the 80 mm Gd/La layered AMR (1.8 °C). The 4-cm AMR bed resulted in relatively similar temperature span to the 80 mm AMR bed span, even though the amount of active MCE materials is lower. The 40 mm AMR bed exhibited much lower pressure drop than the 80 mm AMR bed. As a result, higher flow rate of the heat-exchange fluid could be applied for the 40 mm AMR bed under higher magnetization frequency.